Morals are the guiding principle for common law - Decock, Wim (2014)
Starting from fifty citations from primary sources, this article tries to summarize a recent doctoral thesis on the transformation of traditional ius commune contract law in moral theological treatises from the early modern Catholic world. Firstly, it will be shown how theologians borrowed from the Romano-canon legal tradition to  develop  moral  doctrine.  Secondly, this contribution will try to demonstrate that the traditional conception of contract was fundamentally changed in the works of the theologians. The conclusion will be that theologians developed a doctrine of contracts which redefined contract on the basis of the autonomy of the will, without remaining insensitive to the political, moral and spiritual context in which the homo viator tried to live a God-pleasing life.